GRAPPA-OMERACT initiative to standardise outcomes in psoriatic arthritis clinical trials and longitudinal observational studies - Tillett, W; Orbai, A; Ogdie, A; Leung, Y; Strand, V; Gladman, D; Mease, P; Coates, L (BMJ Publishing Group, 2017)
We read with interest the recent letter by Ramiro et al 1 reporting data from a systematic literature review on the measurement of enthesitis, dactylitis and nail disease in psoriatic arthritis (PsA) clinical trials. The authors highlight the great variety in the outcome measures chosen, cut points and the statistical analysis performed (percentage change, proportion resolved). We are pleased the authors have highlighted this problem and agree with their viewpoints on the clear lack of standardisation of domains and instruments in clinical trials evidenced by the data. Indeed this inconsistency of data reporting has led to significant heterogeneity in both physician-assessed and patient-reported outcomes particularly in the field of PsA. It is the domains of enthesitis, dactylitis, nail disease, as well as skin and axial disease, and the unique impact they subsequently have on physical function and quality of life for patients with PsA, that differentiate PsA from other types of inflammatory arthritis like rheumatoid arthritis. Therefore the accurate assessments of these disease manifestations are of vital importance in drug trials.